2022
DOI: 10.1159/000526154
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Barrett’s Esophagus and Its Risk Factors: A Cross-Sectional Study of 10,122 Subjects at a Japanese Health Examination Center

Abstract: <b><i>Introduction:</i></b> <i>Helicobacter pylori</i> eradication is expected to significantly change the prevalence of Barrett’s esophagus (BE). However, few reports on this relationship exist. We analyzed the risk factors of BE using the current consensus on length of BE considering <i>H. pylori</i> infection status. <b><i>Methods:</i></b> We analyzed 10,122 individuals (5,962 men; mean age = 52.9 ± 9.9 years) who had undergone esophago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…), and status of the drinker (current drinker, former drinker, social drinker, etc .). In an Italian case–control study, 25 the researchers explored the effect of varied alcohol dosages, and types and states of drinking in BE risk, and this study showed U-shaped dose–response relationships between red wine consumption, white wine consumption and BE risk, especially for current drinkers, which means that the BE risk initially decreases as the frequency or years of alcohol consumption increase, but after reaching a certain level, the BE risk starts to increase, and this may explain why social drinking (rarely or sometimes drink) decreased the BE risk when compared to nondrinking, as discovered by the abovementioned study; 43 however, this U-shaped dose–response effect was not observed among other types of drinking, such as beer, and liquor/spirit consumption, which might be caused by different alcohol concentrations and compositions that feature in diverse types of drinking. Though the selection of alcohol intake frequency in the touchscreen questionnaire includes (1) daily or almost daily; (2) three or four times a week; (3) once or twice a week; (4) one to three times a month; (5) special occasions only; (6) never; and (7) prefer not to answer, we were unable to conduct a frequency-stratified or wine type-stratified sub-analysis due to the lack of summary-level GWAS data for different frequencies of alcohol intake or types of wine in our MR analysis.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…), and status of the drinker (current drinker, former drinker, social drinker, etc .). In an Italian case–control study, 25 the researchers explored the effect of varied alcohol dosages, and types and states of drinking in BE risk, and this study showed U-shaped dose–response relationships between red wine consumption, white wine consumption and BE risk, especially for current drinkers, which means that the BE risk initially decreases as the frequency or years of alcohol consumption increase, but after reaching a certain level, the BE risk starts to increase, and this may explain why social drinking (rarely or sometimes drink) decreased the BE risk when compared to nondrinking, as discovered by the abovementioned study; 43 however, this U-shaped dose–response effect was not observed among other types of drinking, such as beer, and liquor/spirit consumption, which might be caused by different alcohol concentrations and compositions that feature in diverse types of drinking. Though the selection of alcohol intake frequency in the touchscreen questionnaire includes (1) daily or almost daily; (2) three or four times a week; (3) once or twice a week; (4) one to three times a month; (5) special occasions only; (6) never; and (7) prefer not to answer, we were unable to conduct a frequency-stratified or wine type-stratified sub-analysis due to the lack of summary-level GWAS data for different frequencies of alcohol intake or types of wine in our MR analysis.…”
Section: Discussionsupporting
confidence: 57%
“…Aaron P Thrift et al 42 found that alcohol was not associated with increased BE risk, and of note, the majority of alcohol drinkers in this study consumed beer. In another cross-sectional study conducted by Dai Kubota et al 43 involving 10 122 enrolled subjects, they even found that social drinking was one of the protective factors of BE (OR: 0.77 (0.68–0.87)), where the definition of “social drinking” in their study was rarely or sometimes drink alcohol. These contradictory findings may be due to the different dosages, and types of alcohol (beer, red wine, white wine, liquor/spirit, etc .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several reports have examined the effects of H. pylori eradication on Barrett’s esophagus. The cross-sectional study by Kubota et al revealed a significantly higher prevalence of Barrett’s esophagus in post- H. pylori eradication patients compared with H. pylori -positive and -negative patients [11], which suggested a positive correlation between eradication therapy and disorder onset. These results differed from our own.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have emerged on the relationship between H. pylori eradication therapy and an increased risk of Barrett's esophagus [9][10][11], although whether these are truly negative correlations remains controversial [12,13]. Moreover, no retrospective cohort studies have addressed Barrett's esophagus elongation by eradication therapy.…”
Section: Introductionmentioning
confidence: 99%